Status Kesehatan Tanah Dengan Metode Selidik Cepat di Areal Pertanaman Teh : Soil Health Status Using A Rapid Test Method In Gambung Tea Plant Area - Wulansari, Restu; Nur Fauzi Athallah, Faris; Winasis Luhur Pambudi , Satria (Jurnal Ecosolum, 2023)
Tea (Camellia sinensis) is an annual plant, which comes from subtropical countries. For few years, tea productivity in West Java Tea Plantation decreased. Soil health is an integration and optimization of physical properties which aimed to increase the productivity and quality of soil, plant, and the environment. Rapid soil investigation was carried out to categorize soil health into healthy, moderate or sick soil based on the soil health index. Soil samples for the rapid soil test taken from North Gambung from block A8, A7, A6, A3, and A11. The parameters observed are to determine the health of the soil chemically, physically and biologically. The chemical parameters were soil organic matter ; soil salinity and soil pH; physically parameters were soil aggregate stability, soil infiltration, and effective depth; biological parameters were vegetation cover; roots condition and worm population. The result of the rapid soil test showed that all area North Gambung are healthy and most of the limiting factors are soil infiltration and roots conditions. In order to overcome the limiting factors, it’s recommended to do forking to get over the total roots problem and addition of organic matter to overcome the soil infiltration problems.